ENGLISH LITERACY CULTURE OF UNIVERSITY LEVEL EFL LEARNERS: HOW LITERATE ARE THEY? - Henny Rahmawati (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2018)
Nowadays, English literacy becomes the hot topic spoken among English practitioners. Literacy embraces four competences including listening, speaking, reading and writing; however, in this particular study the researcher only investigates reading and writing. Many ways have already been and will be conducted to promote such literacy. In this study, the researcher is eager to contribute in giving the springboard particularly for English practitioners to see how the EFL learners’ literacy culture especially in university level and to know the shortages they have faced to build their English literacy culture. The subjects of this study are eighty-two university level students majoring at English education in Unisma. The researcher uses questionnaire as the instrument in gaining the data needed which then were analyzed qualitatively. The result shows that the students’ literacy culture is considered low and needs to improve greatly.